Angiotensin-(1-7) through AT2 receptors mediates tyrosine hydroxylase degradation via the ubiquitin-proteasome pathway - Lopez Verrilli, María Alejandra (2009)
Hypothalamic norepinephrine (NE) release regulates arterial pressure by altering sympathetic nervous system activity. Because angiotensin (Ang) (1-7) decreases hypothalamic NE release and this effect may be correlated with a diminished NE synthesis, we hypothesize that Ang-(1-7) down-regulates tyrosine hydroxylase (TH), the rate-limiting enzyme in catecholamines biosynthesis. We investigated the effect of Ang-(1-7) on centrally TH activity and expression. TH activity was evaluated by the release of tritiated water from (3)H-l-tyrosine. TH expression and phosphorylation were determined by western blot. Hypothalami from normotensive or spontaneously hypertensive rats pre-incubated with Ang-(1-7) showed a significant decrease in TH specific activity. Ang-(1-7) caused a decrease in TH phosphorylation at Ser19 and Ser40 residues. The heptapeptide induced a decrease in TH expression that was blocked by an AT(2) receptor antagonist and not by an AT(1) or Mas receptor antagonist, suggesting the involvement of AT(2) receptors. The proteasome inhibitor MG132 blocked the Ang-(1-7)-mediated TH reduction. In addition, Ang-(1-7) increased the amount of TH-ubiquitin complexes, indicating that the Ang-(1-7)-mediated TH degradation involves ubiquitin conjugation prior to proteasome degradation. We conclude that Ang-(1-7) down-regulates TH activity and expression centrally leading to a decrease in the central NE system activity.